Magnetic modulation of Fano resonances in optically thin terahertz superlattice metasurfaces. (31st December 2021) - Karmakar, Subhajit; Varshney, Ravi; Roy Chowdhury, Dibakar
Abstract: Optically thin metasurfaces operating at sub-skin depth thicknesses are intriguing because of their associated low plasmonic losses (compared to optically thick, beyond skin-depth metasurfaces). However, their applicability is restricted largely because of reduced free space coupling with incident radiations resulting in limited electromagnetic responses. To overcome such limitations, we propose enhancement of effective responses (resonances) in sub-skin depth metasurfaces through incorporation of a magneto-transport (giant magneto resistance) concept. Here, we experimentally demonstrate dynamic magnetic modulation of structurally asymmetric metasurfaces (consisting of superlattice arrangement of thin (∼10 nm each) magnetic (Ni)/nonmagnetic (Al) layers) operating in the terahertz (THz) domain. With increasing magnetic field (applied from 0 to 30 mT approximately, implies increasing superlattice conductivity), we observe stronger confinement of electromagnetic energy at the resonances (both in dipole and Fano modes). Therefore, this study introduces a unique magnetically reconfigurable ability in Fano resonant THz metamaterials, which directly improves their performances operating in the sub-skin depth regime. Our study can be explained by spin-dependent THz magneto-transport phenomena in metals and can stimulate the paradigm for on-chip spin-based photonic technology enabling dynamic magnetic control over compact, sub-wavelength, sub-skin depth metadevices.